2020
DOI: 10.1002/chem.201905057
|View full text |Cite
|
Sign up to set email alerts
|

Carbonyl Activation by Selenium‐ and Tellurium‐Based Chalcogen Bonding in a Michael Addition Reaction

Abstract: In the last years the use of chalcogen bonding-the noncovalent interaction involving electrophilic chalcogen centers-in noncovalentorganocatalysis has received increasedi nterest, particularly regarding the use of intermolecularL ewisa cids. Herein, we present the first use of tellurium-based catalysts for the activation of ac arbonyl compound (and only the second such activation by chalcogen bondingi ng eneral). As benchmark reaction, the Michael-typea ddition between trans-crotonophenone and 1-methylindole (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
79
0
7

Year Published

2020
2020
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 70 publications
1
79
0
7
Order By: Relevance
“…The same catalyst system was subsequently also applied in the Michael addition of indoles to trans ‐crotonophenone . Again, the tellurium‐based chalcogen‐bond donor showed the highest catalytic activity.…”
Section: Chalcogen Bondingmentioning
confidence: 99%
“…The same catalyst system was subsequently also applied in the Michael addition of indoles to trans ‐crotonophenone . Again, the tellurium‐based chalcogen‐bond donor showed the highest catalytic activity.…”
Section: Chalcogen Bondingmentioning
confidence: 99%
“…It is stressed that the focus of the present review is upon the role of intermolecular Se … O contacts and upon the supramolecular aggregation patterns they sustain. In general terms, chalcogen interactions find very practical applications in a range of contexts beyond biology and medicine [16] , [17] , [18] , such as in molecular/anion recognition [19] , [20] , [21] , [22] , catalysts [23] , [24] and materials science [25] , [26] . With this level of activity, it is not surprising there are several authoritative reviews of chalcogen bonding [27] , [28] , [29] , [30] , including reviews of different physiochemical procedures for their detection in phases other than in crystals [31] , [32] , [33] , the primary importance of X-ray crystallographic investigations notwithstanding.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] It could be shown that this bond type can also be used for crystal engineering, [12][13][14] molecular recognition in solution [15][16][17][18][19][20][21] and catalysis. [11,20,[22][23][24][25][26][27][28] Very strong and promising chalcogen bonds are found in electron-poor tellurium compounds such as isotellurazole oxides [21,29] or telluradiazole. [18,30,31] These tellurium-containing systems form strongly associating dimers and oligomers [21] in solution and can therefore be used as recognition units in supramolecular chemistry.…”
Section: Introductionmentioning
confidence: 99%